A checklist of butterflies of Gajurmukhi Village Development Committee, Ilam District, Eastern Nepal - Subba, Bharat Raj (Journal of Natural History Museum, 2008)
A total of 41 speices of butterflies belonging to 31 genera under 7 families reported from Gujurmukhi Village Development Committee, Ilam District eastern Nepal. Specimens were collected during September to October 1995. J. Nat. Hist. Mus. Vol.22, 2005 p.38-40